The role of ultra-thin MnOx co-catalysts on the photoelectrochemical properties of BiVO4 photoanodes. Issue 11 (6th March 2020) - Irani, Rowshanak; Plate, Paul; Höhn, Christian; Bogdanoff, Peter; Wollgarten, Markus; Höflich, Katja; van de Krol, Roel; Abdi, Fatwa F.
Abstract : MnO x suppresses surface recombination by enhancing band bending on BiVO4, but direct contact with the FTO substrate provides shunting pathways. Abstract : Metal oxide semiconductors are promising as photoanodes for solar water splitting, but they typically suffer from poor charge transfer properties due to the slow surface reaction kinetics for oxygen evolution. To overcome this, their surfaces are usually modified by depositing earth-abundant, efficient, and inexpensive water oxidation co-catalysts. While this effort has been successful in enhancing the photoelectrochemical performance, a true understanding of the nature of the improvement is still under discussion. This is due to the fact that the co-catalyst can have multiple functionalities, e.g., accelerating charge transfer, passivating surface states, or modifying band bending. Disentangling these factors is challenging, but necessary to obtain a full understanding of the enhancement mechanism and better design the semiconductor/co-catalyst interface. In this study, we investigate the role of atomic layer deposited (ALD) MnO x co-catalysts and their thickness in the photoelectrochemical performance of BiVO4 photoanodes. Modified MnO x /BiVO4 samples with an optimum thickness of ∼4 nm show higher photocurrent (a factor of >3) as well as lower onset potential (by ∼100 mV) compared to the bare BiVO4 . We combine spectroscopic and photoelectrochemical measurements to unravel the different roles of MnO x and explain the photocurrent trend as a function of the thickness of MnO x . X-ray photoelectron spectroscopy (XPS) studies reveal that the surface band bending of BiVO4 is modified after the addition of MnO x, therefore reducing surface recombination. At the same time, increasing the thickness of MnO x beyond the optimal 4 nm provides shunting pathways, as shown by energy dispersive X-ray scanning transmission electron microscopy (EDX-STEM) and redox electrochemistry. This cancels out the band bending effect, which explains the observed photocurrent trend. Therewith, this study provides additional insights into the understanding of the charge transfer processes occurring at the semiconductor–catalyst interface.